Potential of aqueous extract of Hibiscus sabdariffa calyces as colouring agent in three paediatric oral pharmaceutical formulations - Grace Frimpong, Joseph Adotey, Kwabena Ofori-Kwakye, Samuel Lugrie Kipo, Yaw Dwomo-Fokuo (Journal of Applied Pharmaceutical Science, 2014)
Aqueous extracts of Roselle or Hibiscus sabdariffa L calyces have characteristic intense red colouration due to the presence of anthocyanins which could be utilised as colouring agent in pharmaceutical products. The aim of the current study was to evaluate the potential of aqueous extract of H. sabdariffa calyces as a colouring agent in three pediatric oral pharmaceutical formulations. The colour value of H. sabdariffa calyx extract was determined colorimetrically at λmax 540 nm to be within the BP range of ≥ 0.25. The colour value of H. sabdariffa (0.26) was lower than that of amaranth (0.46), a synthetic commercial pharmaceutical colourant. H. sabdariffa calyx extract retained its colour value within the BP standard for up to six months. The aqueous extract of H. sabdariffa calyces at 33 % w/v was used as colouring agent in paracetamol syrup, diphenhydramine syrup and pediatric cough linctus and the colour stability of the formulations against temperature, light and pH were determined. H. sabdariffa calyx extract was less stable than amaranth to temperature, light and pH when used as a colouring agent. H. sabdariffa calyx extract at 33 % w/v has potential as a colouring agent in pharmaceutical formulations when buffered at pH 5.0, packaged in amber bottles and stored at low temperatures (26-37 °C).
Keywords: Hibiscus sabdariffa calyces, Roselle, anthocyanins, colouring agents, colour value.